Preparation method of polymer solid electrolyte and composite solid electrolyte
The polar solvent is deposited onto the polymer through vapor deposition technology, and the vaporization time is adjusted to improve the ionic conductivity, solving the problem that the ionic conductivity of polymer solid electrolytes in the prior art is difficult to improve, and achieving efficient and safe electrolyte performance.
Patent Information
- Application Number
- CN202380063664.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-12
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-11
AI Technical Summary
The ionic conductivity of existing polymer solid electrolytes is difficult to increase to above 0.1 mS/cm, and in the process of improving the ionic conductivity, there may be safety problems and the risk of mechanical properties degradation.
By vapor-phase deposition of polar solvents onto the polymer, gaseous polar compounds are formed and the vaporization time is adjusted during vapor-phase deposition to improve the ionic conductivity of the polymer solid electrolyte.
It is achieved that the ionic conductivity of the polymer solid electrolyte is significantly improved without damaging the mechanical properties, ensuring the safety and efficiency of the electrolyte.
Smart Images

Figure CN119816974A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0132778 filed on October 14, 2022, and Korean Patent Application No. 10-2023-0136062 filed on October 12, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present invention relates to a method for preparing a polymer solid electrolyte and a method for preparing a composite solid electrode. Background Art
[0004] Lithium-ion batteries using liquid electrolytes have a structure in which the negative electrode and the positive electrode are defined by a separator, so when the separator is damaged by deformation or external impact, a short circuit may occur, causing dangers such as overheating or explosion. Therefore, it can be said that the development of a solid electrolyte that can ensure safety is a very important issue in the field of lithium-ion secondary batteries.
[0005] The advantages of lithium secondary batteries using solid electrolytes are that their safety is enhanced, electrolyte leakage is prevented to improve battery reliability, and thin batteries are made possible. In addition, lithium metal can be used as a negative electrode to increase energy density, so in addition to compact secondary batteries, it is expected to be applied to high-capacity secondary batteries for electric vehicles, and is therefore attracting attention as a next-generation battery.
[0006] Among solid electrolytes, composite electrolytes of polyethylene oxide (PEO) and lithium salts have the advantage of having higher ignition stability than conventional liquid electrolytes, but their limitation is that it is difficult to prepare polymer solid electrolytes with improved ionic conductivity due to the high crystallinity of polyethylene oxide (PEO). In other words, the high crystallinity of the polymer hinders the chain mobility of the polymer chain, and therefore, the movement of lithium ions in the polymer solid electrolyte is restricted, which makes it difficult to improve the ionic conductivity of the polymer solid electrolyte.
[0007] In order to overcome the limitations of conventional polymer solid electrolytes, attempts have been made to change the structure of crystalline polymers or add separate plasticizers to the polymers to improve the mobility of polymer chains, thereby enhancing the ionic conductivity of polymer solid electrolytes. However, solid polymer electrolytes prepared by using such structural deformation of polymers and adding plasticizers may have difficulty in increasing the ionic conductivity above the 0.1 mS / cm level.
[0008] Attempts have been made to increase ionic conductivity by adding a liquid electrolyte or solvent directly to a polymer solid electrolyte in a liquid state, but this technology can be classified as a semi-solid-state battery electrolyte in which solid and liquid coexist rather than a pure solid electrolyte for an all-solid-state battery, and there may still be safety issues caused by leakage of the liquid electrolyte, etc., and the improvement in ionic conductivity may not be sufficient.
[0009] Therefore, in addition to polymer solid electrolytes prepared by changing the structure of the polymer, adding a separate plasticizer, or immersing the solid electrolyte in a liquid electrolyte, it is necessary to develop a technology that can improve the ionic conductivity of the electrolyte as a simple solid electrolyte for all-solid-state batteries.
[0010] [Prior art literature]
[0011] [Patent Document]
[0012] (Patent Document 1) Japanese Patent Application Publication No. 1994-124713 Summary of the invention
[0013] [Technical issues]
[0014] The object of the present disclosure is to provide a method for preparing a polymer solid electrolyte, which can not only prepare a polymer solid electrolyte having improved ionic conductivity by forming a gaseous polar compound by vapor-depositing a polar solvent onto a polymer and thereby vapor-depositing a very small amount of solvent, but also can adjust the vaporization time during the preparation process to maximize the improvement in ionic conductivity.
[0015] Another object of the present disclosure is to provide a method for preparing a composite solid electrode, which can adjust the vaporization time during the process of preparing a composite solid electrolyte by vapor deposition, thereby maximizing the improvement of ion conductivity.
[0016] [Technical solution]
[0017] According to one embodiment of the present disclosure, a method for preparing a polymer solid electrolyte is provided, the method comprising the following steps: (S1) preparing a polymer in which a PEO (polyethylene oxide)-based copolymer containing a crosslinkable functional group is crosslinked; and (S2) vapor-depositing a polar solvent onto the polymer prepared in step (S1), wherein the vapor-deposition step is performed for a time period that satisfies the following equation 1:
[0018] <Equation 1>
[0019]
[0020] Where, in equation 1,
[0021] σi (t) is the ionic conductivity of the polymer solid electrolyte as a function of vapor deposition time,
[0022] σ i,0 is the maximum ionic conductivity, which is greater than 0.1 mS / cm and less than 1 mS / cm,
[0023] t is the vapor deposition time, and
[0024] τ is the relaxation time of the polymer chain, which is 12 hours or more and 120 hours or less.
[0025] In the preparation method, step (S1) is performed in the presence of one or more additives selected from the group consisting of a crosslinking agent and an initiator, so that a crosslinking step can be performed.
[0026] Furthermore, in the preparation method, a lithium salt may be further added in step (S1) or before step (S1).
[0027] Meanwhile, in the preparation method, the crosslinkable functional group contained in the PEO-type copolymer may be bonded to the chain of the PEO-type copolymer via an alkylene linker having 0 to 10 carbon atoms or an alkylene oxide linker (wherein the alkylene linker having 0 carbon atoms represents a single bond), and may be a functional group selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.
[0028] In a specific embodiment, the PEO (polyethylene oxide)-based copolymer containing a cross-linkable functional group may be a copolymer containing repeating units of the following Chemical Formulas 1 to 3:
[0029] [Chemical formula 1]
[0030]
[0031] [Chemical formula 2]
[0032]
[0033] [Chemical formula 3]
[0034]
[0035] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k-R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms, R2 represents a substituent formed by bonding to the polymer chain via an alkylene linker having 0 to 10 carbon atoms or an oxyalkylene linker (wherein the alkylene linker having 0 carbon atoms represents a single bond) of one or more crosslinkable functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group and an allyl group, and l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.
[0036] Meanwhile, in step (S2) of the preparation method, vapor of the polar solvent may be deposited onto the polymer such that the content of the polar solvent is 0.1 wt% or more and less than 10 wt% based on the total weight of the polymer solid electrolyte.
[0037] In addition, the polar solvent corresponds to a polar compound deposited in a gaseous state and contained in the polymer solid electrolyte, and may include at least one selected from the group consisting of a carbonate solvent and a sulfonyl solvent. More specifically, the polar solvent may include at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane.
[0038] Meanwhile, according to another embodiment of the present disclosure, a method for preparing a composite solid electrolyte comprising a polymer solid electrolyte and a ceramic compound is provided. This preparation method comprises the following steps: (S1) mixing a PEO (polyethylene oxide) copolymer containing a crosslinkable functional group with a ceramic compound, and then subjecting the PEO copolymer contained in the mixture to a crosslinking reaction; and (S2) vapor-depositing a polar solvent onto the mixture containing the polymer crosslinked in step (S1),
[0039] The vapor deposition step is performed for a period of time satisfying the following equation 2:
[0040] <Equation 2>
[0041]
[0042] Where, in equation 2,
[0043] σ i (t) is the ionic conductivity of the composite solid electrolyte as a function of vapor deposition time,
[0044] σ i,0 is the maximum ionic conductivity, which is greater than 1 mS / cm and less than 10 mS / cm,
[0045] t is the vapor deposition time, and
[0046] τ is the relaxation time of the polymer chain, which is 12 hours or more and 120 hours or less.
[0047] [Beneficial Effects]
[0048] According to the preparation method of the polymer solid electrolyte and the composite solid electrolyte disclosed in the present invention, a gaseous polar solvent (or polar compound) can be included in the three-dimensional network structure of the solid electrolyte formed by cross-linking through vapor deposition, or can be bonded to the cross-linked polymer.
[0049] Therefore, a small amount of polar solvent is gradually injected into the solid electrolyte in a gaseous state, which can prevent gelation, delay the relaxation time of the internal polymer chains, and improve the mobility of the polymer chains, thereby improving the ionic conductivity without deteriorating the mechanical properties.
[0050] In addition, the ionic conductivity increases in proportion to the vapor deposition time at the beginning of the vapor deposition process, and then shows a trend of converging to a specific ionic conductivity as a certain time passes. Therefore, by adjusting the vapor deposition time according to this trend, the effect of improving the ionic conductivity of the polymer solid electrolyte or the composite solid electrolyte can be maximized.
[0051] In addition, polymer solid electrolytes and composite solid electrolytes can enhance the mobility of polymer chains and exhibit further improved ionic conductivity while maintaining the original structural features of the polymer without deforming or destroying the material.
[0052] In addition, the composite solid electrolyte further comprising a ceramic compound may exhibit further improved ionic conductivity due to uniform distribution of such a ceramic compound.
[0053] In addition, polymer solid electrolytes and composite solid electrolytes contain extremely small amounts of gaseous polar compounds and thus can exhibit improved ionic conductivity and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 Graph showing the change in ionic conductivity of the polymer solid electrolyte during solvent vapor deposition in Example 1 as a function of vapor deposition time.
[0055] Figure 2 is a graph showing the change in ionic conductivity of the composite solid electrolyte during the solvent vapor deposition process of Example 2 as a function of vapor deposition time.
[0056] Figure 3 : is a graph showing the change in ionic conductivity of the polymer solid electrolyte during solvent immersion of Comparative Example 1 with immersion time.
[0057] Figure 4 is a graph showing the change in ionic conductivity of the composite solid electrolyte during solvent immersion in Comparative Example 2 as a function of immersion time. DETAILED DESCRIPTION
[0058] Hereinafter, for a better understanding of the present disclosure, specific embodiments will be described in more detail.
[0059] The terms or words used in the specification and the appended claims should not be construed as limited to the ordinary or dictionary meanings, but should be interpreted in the present disclosure with meanings and concepts consistent with the technical ideas of the present disclosure based on the principle that the inventor can appropriately define the concepts of the terms to appropriately describe his own invention in the best manner.
[0060] Regarding the term "bond" used herein, i.e., the conformation of the polar compound "bonded" to the polymer chain (e.g., the chain of the PEO-type copolymer), the term "bond" broadly refers to the conformation of the state in which the gaseous polar compound (which is a polar solvent molecule) remains fixed to the polymer chain by the vapor deposition of the polar solvent. In other words, the "bond" is not limited to a specific type of physical bond, chemical bond, etc., but refers to a state of being fixed by various bonds including physical bonds, chemical bonds, etc., or a state of being simply attached and fixed (e.g., by adsorption, etc.), or a state of being contained in a three-dimensional network structure formed by polymer cross-linking and being located near the polymer chain or cross-linking structure and fixed.
[0061] The term "three-dimensional network structure" used herein is a structure including a three-dimensional framework and an internal space formed by the framework, wherein the framework may include polymer chains including cross-links formed by cross-linkable functional groups, for example, cross-links between cross-linkable functional groups and / or cross-links between cross-linkable functional groups and cross-linking agents. The three-dimensional network structure may also be referred to as a cross-linked structure.
[0062] In the present disclosure, the polar compound (polar solvent) exists in a "gaseous state" or is contained in a polymer or composite solid electrolyte, indicating that, unlike the case where the polar solvent or the electrolyte containing the polar solvent is injected in a liquid state, the polar compound is deposited in a vapor state, and the polar compound exists in a state different from the liquid-injected electrolyte just after the solid electrolyte is prepared or during the charging and discharging process of the all-solid-state secondary battery containing the solid electrolyte. However, depending on the storage or operating conditions of the solid electrolyte and / or the secondary battery, the vapor-deposited polar compound may have a partially or temporarily liquefied state. Even in this case, the vapor-deposited polar compound exhibits higher mobility than the polar solvent injected in a liquid state, and exhibits a state different from the liquid polar solvent, which can also be considered to be present or contained in the above-mentioned "gaseous state".
[0063] As used herein, the term "polymer solid electrolyte" includes as essential components (i) a polymer comprising a polyethylene oxide (PEO)-based copolymer containing a cross-linkable functional group and a polar compound, or refers to (ii) a polymer solid electrolyte further comprising a ceramic compound in the above (i). (ii) The polymer solid electrolyte further comprising a ceramic compound in the above (i) may be referred to as a "composite solid electrolyte".
[0064] On the other hand, conventionally, in order to improve the ionic conductivity of the solid electrolyte, the solid electrolyte is immersed in or loaded on a liquid electrolyte or solvent, or the liquid electrolyte or solvent is directly injected into the solid electrolyte in a liquid state. When the liquid electrolyte or solvent is directly added to the solid electrolyte in this way, it has the effect of improving the ionic conductivity of the solid electrolyte, but this is only based on the high ionic conductivity of the liquid itself to improve the ionic conductivity of the solid electrolyte, and the degree of improvement is not sufficient, and a large amount of liquid electrolyte needs to be injected. In other words, since the conduction of lithium ions is achieved by the liquid electrolyte added to the solid electrolyte rather than the inherent physical properties of the solid electrolyte, it is far from improving the physical properties of the solid electrolyte itself. In addition, when the liquid electrolyte or solvent is directly added or injected into the polymer solid electrolyte in liquid form, there is the following problem: due to unexpected side reactions between the polymer and the liquid phase, the structure of the solid electrolyte collapses, such as damage to the polymer chain or breakage of the polymer internal bond, or the ionic conductivity is reduced.
[0065] In addition, when solvents or liquid electrolytes are directly injected into solid electrolytes, the liquid molecules diffuse rapidly within the solid electrolyte, rapidly causing relaxation of the polymer chains and promoting surface gelation, which may lead to a decrease in mechanical properties, and problems such as liquid leakage of the liquid electrolyte may not be completely solved.
[0066] In addition, Japanese Patent Application Laid-Open No. 1994-124713 as a prior art discloses a technique of vapor-depositing a solvent onto a general PEO (polyethylene oxide) polymer. In this case, there is a problem that the internal structure of the polymer collapses due to lack of a cross-linked structure and ion conductivity cannot be ensured.
[0067] Therefore, the present inventors have applied a method of vapor-depositing a polar compound derived from a polar solvent onto a polymer solid electrolyte containing a polymer cross-linked with a PEO (polyethylene oxide) type copolymer modified with a cross-linkable functional group. The polymer solid electrolyte prepared in this manner comprises: a polymer containing a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group; and a polar compound, wherein at least a portion of the cross-linkable functional groups form cross-links with each other so that the polymer forms a three-dimensional network structure, and wherein the polar compound is contained in the three-dimensional network structure in a gaseous state, or can represent a structure bonded to a polymer chain.
[0068] It was confirmed that the polymer solid electrolyte exhibits improved ion conductivity even when containing a trace amount of gaseous polar compounds derived from polar solvents. It is expected that this is because the gaseous polar compounds affect the physical properties such as crystallinity of the PEO-based copolymer and increase the chain mobility of the polymer chain, thereby improving the conductivity of lithium ions contained in the polymer solid electrolyte.
[0069] Next, a method for preparing a polymer solid electrolyte according to a specific embodiment will be described in detail.
[0070] Preparation method of polymer solid electrolyte
[0071] According to one disclosed embodiment, a method for preparing a polymer solid electrolyte is provided, the method comprising the following steps: (S1) preparing a polymer in which a PEO (polyethylene oxide)-based copolymer containing a crosslinkable functional group is crosslinked; and (S2) vapor-depositing a polar solvent onto the polymer prepared in step (S1), wherein the vapor-deposition step is performed for a time period that satisfies the following equation 1:
[0072] <Equation 1>
[0073]
[0074] Where, in equation 1,
[0075] σ i (t) is the ionic conductivity of the polymer solid electrolyte as a function of vapor deposition time,
[0076] σ i,0 is the maximum ionic conductivity, which is greater than 0.1 mS / cm and less than 1 mS / cm,
[0077] t is the vapor deposition time, and
[0078] τ is the relaxation time of the polymer chain, which is 12 hours or more and 120 hours or less.
[0079] In this preparation method, Equation 1 defines the relationship between the vapor deposition time (t) and the ionic conductivity (σ i (t)) and is defined so as to eliminate the influence of other variables in the vapor deposition process. In general, τ may vary depending on the temperature, but in order to ensure that the vapor deposition time (t) and ionic conductivity (σ) of Equation 1 are consistent, i (t)) does not change according to temperature, and τ can be defined as a constant as described below. From a physical point of view, τ can be the time required for a polymer system in equilibrium at a certain temperature to reach another equilibrium state after it is transformed into a non-equilibrium state due to an external perturbation.
[0080] In τ of Equation 1, vapor deposition of the polar solvent corresponds to an external disturbance, and the ionic conductivity observed at a time point (t=τ) when the vapor deposition time (t) in Equation 1 is τ may be a signal indicating that the polymer system has reached a stable equilibrium state.
[0081] The relaxation time can usually vary depending on the temperature. The ionic conductivity of polymer solid electrolytes shows a behavior of increasing together with the increase in temperature. Therefore, when the vapor deposition process is carried out at high temperature, the increase in ionic conductivity may be the result of the combined effect of temperature and vapor deposition effects. In order to eliminate the coupling effect in the experimental results and accurately grasp the relaxation time of the polymer chain induced by vapor deposition, the vapor deposition process can be carried out at room temperature.
[0082] For example, vapor deposition can generate polar solvent vapor in a closed chamber to deposit polar solvent gas molecules on a polymer. The polar solvent gas molecules are deposited on the polymer in a state where the interior of the closed chamber is saturated with polar solvent vapor.
[0083] In addition, the vapor deposition process is based on the principle of allowing a minimum amount of gas molecules that can move freely within a closed system to penetrate into the interior of the polymer, so even if the area where the polar solvent evaporates and the area where the vapor is deposited are different, the relaxation time can be effectively extended.
[0084] The vapor deposition time may affect the polymer chain structure of the polymer solid electrolyte in which the polar solvent is deposited onto the polymer with the polar compound, and may ultimately affect the ionic conductivity of the polymer solid electrolyte.
[0085] Therefore, according to Equation 1, the correlation between the vapor deposition time and the ionic conductivity of the polymer solid electrolyte is defined in a state where the influence of variables in the vapor deposition process is eliminated, so that the ionic conductivity of the polymer solid electrolyte finally prepared can be controlled in the process of preparing the polymer solid electrolyte. For example, in the preparation method of one embodiment, vapor deposition can be performed within a time period that satisfies Equation 1 in consideration of the maximum ionic conductivity to be achieved, so as to prepare a polymer solid electrolyte exhibiting improved ionic conductivity.
[0086] Next, a preparation method according to one embodiment will be described in more detail for each step.
[0087] In step (S1), a polymer cross-linked with a PEO (polyethylene oxide)-based copolymer containing a cross-linkable functional group may be prepared.
[0088] The cross-linking reaction in step (S1) may be performed in the presence of at least one additive selected from the group consisting of a cross-linking agent and an initiator.
[0089] Furthermore, in order to form a polymer solid electrolyte, a lithium salt may be further added to the PEO-based copolymer having a cross-linkable functional group during the cross-linking reaction step ( S1 ) or in a previous step thereof.
[0090] Furthermore, the cross-linking bond may be formed in the process of coating a polymer solution containing a PEO-based copolymer on a substrate to form a coating film and then drying the coating film.
[0091] Specifically, the polymer solution may be prepared by mixing the PEO-based copolymer in a solvent, and in addition, the solution may be prepared by mixing and dissolving a cross-linking agent, an initiator, and / or a lithium salt together.
[0092] The solvent is not particularly limited, as long as it can be mixed and dissolved with the PEO-based copolymer, cross-linking agent, initiator and / or lithium salt and can be easily removed by a drying process. For example, the solvent can be acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropanol, dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP) or N, N-dimethylformamide (DMF) etc. This solvent is a solvent used as a reaction medium for forming a cross-linked bond, which is different from the polar solvents etc. contained in the liquid electrolyte, and is completely removed by drying etc. after cross-linking.
[0093] Considering the degree that the forming process of preparing polymer solid electrolyte can be carried out smoothly, the concentration of polymer solution can be appropriately adjusted. Specifically, the concentration of polymer solution can refer to the concentration (weight %) of polymer in polymer solution. The concentration of polymer can be the concentration of PEO-based copolymer. For example, the concentration of polymer solution can be 5 weight % to 20 weight %, specifically, it can be more than 5 weight %, more than 7 weight % or more than 9 weight % and less than 13 weight %, less than 17 weight % or less than 20 weight %. If the concentration of polymer solution is less than 5 weight %, the concentration may be too dilute, and the mechanical strength of polymer solid electrolyte may be reduced, or when coated on substrate, it may flow downward. If the concentration of polymer solution is greater than 20 weight %, it is difficult to dissolve lithium salt in polymer solution with desired concentration, viscosity will be high, solubility will be low, which makes it difficult to apply lithium salt in the form of uniform film.
[0094] The substrate is not particularly limited as long as it can be used as a support for coating. For example, the substrate can be SUS (stainless steel), polyethylene terephthalate film, polytetrafluoroethylene film, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, vinyl chloride copolymer film, polyurethane film, ethylene-vinyl acetate film, ethylene-propylene copolymer film, ethylene-ethyl acrylate copolymer film, ethylene-methyl acrylate copolymer film or polyimide film.
[0095] In addition, the coating method is not particularly limited as long as it can form a coating film by coating the polymer solution on the substrate. For example, the coating method can be rod coating, roller coating, spin coating, slit coating, die coating, blade coating, comma coating, slit die coating, lip coating, spray coating or solution casting.
[0096] The coating film formed on the substrate by the coating method can be formed into a polymer from which the residual solvent is completely removed by a drying process. Drying can be divided into a primary drying process and a secondary drying process to prevent the polymer from shrinking due to the rapid evaporation of the solvent. The primary drying process can remove part of the solvent by room temperature drying, and the secondary drying process can completely remove the solvent by vacuum high temperature drying. High temperature drying can be carried out at a temperature of 80°C to 130°C. If the high temperature drying temperature is less than 80°C, the residual solvent cannot be completely removed, and if the high temperature drying temperature is greater than 130°C, the polymer will shrink, which makes it difficult to form a uniform electrolyte membrane.
[0097] In one embodiment of the present disclosure, the crosslinkable functional group may be composed of two or more. The crosslinkable functional groups may be the same or different from each other, and preferably may be different. When the crosslinkable functional groups are different, multiple repeating units each containing these functional groups may be included. In addition, when multiple crosslinkable functional groups are included, the mobility and ionic conductivity of the polymer chain can be more easily controlled.
[0098] The crosslinkable functional group refers to a functional group capable of forming a crosslink bond between crosslinkable functional groups and / or forming a crosslink bond with each other through a crosslinking agent, and may be bonded to the main chain of the polymer chain in the form of a side chain.
[0099] Specifically, the crosslinkable functional group can be directly bonded to the main chain of the PEO-based copolymer, or can be bonded through an alkylene or oxyalkylene linker. Therefore, the crosslinkable functional group can be bonded through an alkylene linker or oxyalkylene linker having 0 to 10 carbon atoms (wherein the alkylene linker having 0 carbon atoms represents a single bond), and can be at least one selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.
[0100] In a more specific example, the PEO-based copolymer containing a cross-linkable functional group may be a copolymer containing repeating units of the following Chemical Formulas 1 to 3:
[0101] [Chemical formula 1]
[0102]
[0103] [Chemical formula 2]
[0104]
[0105] [Chemical formula 3]
[0106]
[0107] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms,
[0108] R2 represents a substituent formed by bonding to the polymer chain one or more crosslinkable functional groups selected from the group consisting of hydroxyl, carboxyl, isocyanate, nitro, cyano, amine, amide, epoxy and allyl groups via an alkylene linker having 0 to 10 carbon atoms or an oxyalkylene linker (wherein an alkylene linker having 0 carbon atoms represents a single bond), and
[0109] l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.
[0110] For example, the cross-linkable functional group of R2 can form a polymer in the form of a matrix having a three-dimensional network structure formed by cross-linking bonds. The three-dimensional network structure is formed by cross-linking bonds, thereby improving the mechanical properties of the polymer solid electrolyte, and gaseous polar compounds can be included or bonded in this three-dimensional network structure to provide a polymer solid electrolyte of one embodiment with improved ionic conductivity.
[0111] In addition, it is apparent that the PEO-based copolymer may include two or more repeating units of Chemical Formula 3, wherein R2 are cross-linkable functional groups different from each other, and may also include one or more repeating units of Chemical Formula 2.
[0112] When l, m and n are each less than 1, it is difficult to form a polymer due to the small molecular weight, and when l, m and n are each greater than 1000, the solubility during the preparation of the polymer solution decreases due to the increase in viscosity, and the molding for preparing the polymer solid electrolyte may become difficult. In particular, when the number of repetitions of the repeating unit containing a crosslinkable functional group in l, m and n is greater than 1000, the degree of crosslinking increases excessively, the mobility of the polymer chain may decrease, and the ionic conductivity of the polymer solid electrolyte may decrease.
[0113] As used herein, "hydroxy" refers to an -OH group.
[0114] As used herein, "carboxyl" refers to a -COOH group.
[0115] As used herein, "isocyanate" refers to a -N=C=O group.
[0116] As used herein, "nitro" refers to a -NO2 group.
[0117] As used herein, "cyano" refers to a -CN group.
[0118] As used herein, "amide" refers to -C(=O)NR'R", wherein R' and R" can each independently be hydrogen or C1 to C5 alkyl, or R' and R" together with the N atom to which they are attached can form a heterocycle having 4 to 8 carbon atoms in the ring structure.
[0119] As used herein, "amino" may be selected from the group consisting of monoalkylamino, monoarylamino, monoheteroarylamino, dialkylamino, diarylamino, diheteroarylamino, alkylarylamino, alkylheteroarylamino, and arylheteroarylamino, and the carbon number thereof is not particularly limited, but is preferably 1 to 30. Specific examples of amine include methylamino, dimethylamino, ethylamino, diethylamino, phenylamino, naphthylamino, biphenylamino, dibiphenylamino, anthracenylamino, 9-methyl-anthrylamino, diphenylamino, phenylnaphthylamino, ditolylamino, phenyltolylamino, triphenylamino, biphenylnaphthylamino, phenylbiphenylamino, biphenylfluorenylamino, phenyltriphenyleneamino, and biphenyltriphenyleneamino, but are not limited thereto. In addition, "amino" refers to -NH2.
[0120] As used herein, "allyl" refers to a -CH2-CH=CH2 group.
[0121] The weight average molecular weight (Mw) of the copolymer containing chemical formula 1 to 3 can be 100,000g / mol to 2,000,000g / mol, specifically, it can be 100,000g / mol or more, 200,000g / mol or more, or 300,000g / mol or more and 1,600,000g / mol or less, 1,800,000g / mol or less, or 2,000,000g / mol or less. If the weight average molecular weight (Mw) of the copolymer is less than 100,000g / mol, the mechanical properties of the polymer solid electrolyte to be prepared may not be met. If the weight average molecular weight (Mw) of the copolymer is greater than 2,000,000g / mol, the solubility during the preparation of the polymer solution is reduced due to increased viscosity, and the molding for preparing the polymer solid electrolyte may become difficult. In addition, due to the increase in crystallinity and the reduction in chain mobility inside the polymer solid electrolyte, the ionic conductivity of the polymer solid electrolyte may be reduced.
[0122] In particular, when the number of repetitions of the repeating unit of Chemical Formula 3 containing a crosslinkable functional group in l, m, and n is greater than 1000, the degree of crosslinking increases excessively and the mobility of the polymer chain decreases, which may result in a decrease in the ionic conductivity of the polymer solid electrolyte.
[0123] Furthermore, the copolymer may be a random copolymer or a block copolymer.
[0124] In a specific embodiment of the present disclosure, the polymer solid electrolyte may include crosslinks between crosslinkable functional groups. In addition, the polymer solid electrolyte may further include a crosslinking agent to form crosslinks between the crosslinking agent and the crosslinkable functional groups. For example, at least a portion of the crosslinkable functional groups may form crosslinks with each other via a crosslinking agent, thereby forming the above-mentioned three-dimensional network structure.
[0125] The crosslinking bond between the crosslinkable functional groups may be a urethane crosslinking bond, an ester crosslinking bond, a hydrogen bond, a bond formed by a radical polymerization reaction of a vinyl group at the end of an allyl group (-CH2-CH=CH2), etc., but is not limited to these examples.
[0126] In addition, when a crosslinking agent is added during the preparation of the polymer solid electrolyte, a crosslinking bond between the crosslinking agent and the crosslinkable functional group can be formed. The crosslinking bond can be a hydrogen bond, a bond formed by Lewis acid-base interaction, an ionic bond, a coordination bond, or a bond formed by free radical polymerization.
[0127] The crosslinking agent is not particularly limited as long as it is a multifunctional crosslinking agent that can form a crosslinked bond with a crosslinkable functional group. For example, the crosslinking agent can be selected from trimethylolpropane trimethacrylate, poly(ethylene glycol) diacrylate, poly(ethylene glycol) dimethacrylate, ethylene glycol dimethacrylate (hereinafter referred to as "EGDMA"), 1,3-diisopropenylbenzene (DIP), 1,4-diacrylpiperazine, 2-(diethylamino)ethyl methacrylate, 2,6-bisacrylaminopyridine, 3-(acryloyloxy)-2-hydroxypropyl methacrylate, 3,5-bis(acryloylamino)benzoic acid, 3-aminopropyl triethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-methacryloxypropyl trimethoxysilane, bis-(1- (tert-butylperoxy)-1-methylethyl)-benzene, dicumyl peroxide, dimethacrylate, divinylbenzene, malein glycol acrylate, glycidyl methacrylate, hydroxyquinoline, i-phenyldiethoxysilane, malein glycol acrylate, methylenebisacrylamide, N,N'-1,4-phenylenedipropyleneamine, N,O-bisacryloyl-phenylalaninol, N,O-bismethacryloylethanolamine, pentaerythritol triacrylate, phenyltrimethoxysilane, tetramethoxysilane, tetramethylene compounds, tetraethoxysilane and triallyl isocyanurate. One or more multifunctional crosslinking agents, for example, a polyvalent compound having two or more functionalities.
[0128] In addition, the content of the crosslinking agent may be 1 to 30 parts by weight based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group. If the content of the crosslinking agent is less than 1 part by weight, crosslinking with the crosslinkable functional group may not be sufficiently achieved, and if the content of the crosslinking agent is greater than 30 parts by weight, excessive crosslinking may occur, the mobility of the polymer chain may decrease, and thus the ionic conductivity may decrease.
[0129] In one embodiment of the present disclosure, the initiator can induce a free radical polymerization reaction between the crosslinkable functional groups to form a crosslinking bond between the crosslinkable functional groups. The functional group capable of free radical polymerization can be a functional group containing a vinyl group at the end, such as an allyl group.
[0130] The initiator is not particularly limited as long as it is an initiator that can induce a free radical polymerization reaction between crosslinkable functional groups. For example, the initiator may include at least one selected from the group consisting of benzoyl peroxide, azobisisobutyronitrile, lauroyl peroxide, cumene hydroperoxide, diisopropylphenyl-hydroperoxide, tert-butyl hydroperoxide, p-methane hydroperoxide and 2,2'-azobis(2-methylpropionitrile).
[0131] Based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group, the initiator may be used in an amount of 0.5 to 2 parts by weight. When the initiator is used within the above range, it may be able to induce a free radical polymerization reaction between the crosslinkable functional groups and effectively form a crosslink bond.
[0132] In one embodiment of the present disclosure, the lithium salt is contained in the internal space between the polymer chains in a dissociated ionic state, so that the ionic conductivity of the polymer solid electrolyte can be improved. At least a portion of the cations and / or anions dissociated from the lithium salt exist in a state of being bonded to the polymer chain and can exhibit mobility during charge / discharge of the battery.
[0133] The lithium salt may include (CF3SO2)2NLi (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), (FSO2)2NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, LiC(CF3SO2)3, lithium chloroborane, lower aliphatic carboxylic acid lithium and at least one of the group consisting of lithium tetraphenylborate.
[0134] In addition, based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group, the content of the lithium salt may be 25 to 45 parts by weight. Specifically, the content may be more than 25 parts by weight, more than 30 parts by weight, or more than 35 parts by weight, or less than 40 parts by weight, or less than 45 parts by weight. If the content of the lithium salt is less than 25 parts by weight, the ionic conductivity of the polymer solid electrolyte may be reduced, and if the content of the lithium salt exceeds 45 parts by weight, the mechanical strength may be reduced.
[0135] Meanwhile, in step (S2), the polar solvent may be vapor-deposited onto the polymer prepared in step (S1) to prepare a polymer solid electrolyte in which polar solvent gas molecules are bonded to polymer chains or gaseous polar compounds are contained in the internal space of polymer chains, for example, in a three-dimensional network structure. At this time, the gas molecules of the polar solvent may correspond to the polar compound.
[0136] Furthermore, in the manufacturing method of one embodiment, the vapor deposition step may be performed for a period of time satisfying the following equation 1:
[0137] <Equation 1>
[0138]
[0139] Where, in equation 1,
[0140] σ i (t) is the ionic conductivity of the polymer solid electrolyte as a function of vapor deposition time,
[0141] σ i,0 is the maximum ionic conductivity, which is greater than 0.1 mS / cm and less than 1 mS / cm,
[0142] t is the vapor deposition time, and
[0143] τ is the relaxation time of the polymer chain, which is 12 hours or more and 120 hours or less.
[0144] σ i (t) (mS / cm) refers to the ionic conductivity of the polymer solid electrolyte as a function of the vapor deposition time. The ionic conductivity increases in proportion to the vapor deposition time (t) at the beginning of the vapor deposition process, however, after a certain vapor deposition time (t), it shows a tendency to converge to a specific ionic conductivity value while the increase amplitude decreases. Preferably, vapor deposition can be performed until σ i (t) becomes equal to σ i,0 Same value.
[0145] σ i,0 Refers to the maximum ionic conductivity of the polymer solid electrolyte. The maximum ionic conductivity refers to the ionic conductivity that occurs when the polymer solid electrolyte has a complete structure without any defects. i,0 can be used as a fitting parameter.
[0146] t is the vapor deposition time, which may refer to the time elapsed from the time point when the vapor deposition starts. The method or device for measuring the vapor deposition time is not particularly limited. For example, the vapor deposition time may be measured using various means that can determine the time at a specific time point.
[0147] τ refers to the relaxation time of the polymer chain, which is the time required from the time when the polar solvent begins to be vapor-deposited to the time when the polymer chain is deformed by the polar solvent and then returns to the equilibrium or normal state. For example, an exemplary method and conditions for measuring relaxation time are described in "Tapabrata Dam et al., "The ionic transport mechanism and coupling between the ion conduction and segmental relaxation processes of PEO 20 -LiCF3SO3 based ion conducting polymer clay composites”, Phys. Chem. Chem. Phys 18, 19955-19965 (2016).
[0148] In general, relaxation time may refer to the time required for a polymer system in equilibrium to reach another equilibrium state after it is transformed into a non-equilibrium state due to an external disturbance.
[0149] In τ of Equation 1, vapor deposition of the polar solvent corresponds to an external disturbance, and the ionic conductivity observed at a time point (t=τ) when the vapor deposition time (t) in Equation 1 is τ may be a signal indicating that the polymer system has reached a stable equilibrium state.
[0150] The relaxation time can usually vary depending on the temperature. The ionic conductivity of polymer solid electrolytes shows a behavior of increasing together with the increase in temperature. Therefore, when the vapor deposition process is carried out at high temperature, the increase in ionic conductivity may be the result of the combined effect of temperature and vapor deposition effects. In order to eliminate the coupling effect in the experimental results and accurately grasp the relaxation time of the polymer chain induced by vapor deposition, the vapor deposition process can be carried out at room temperature.
[0151] τ can be used as a fitting parameter and can range from 12 hours to 120 hours.
[0152] Vapor deposition can be performed by contacting the polymer with the vapor of a polar solvent generated at room temperature or by heating and permeating into the polymer. In this way, the gaseous polar compound is uniformly diffused on the surface and / or inside of the polymer by placing the solvent at room temperature or by heating to vaporize the solvent, so that the gas molecules of the polar compound can be bonded to the polymer chain, or can be contained in the internal space of the polymer chain in a uniformly dispersed or diffused form.
[0153] When the polar solvent is placed at room temperature during vapor deposition, a trace amount of the low-boiling-point polar solvent can slowly vaporize at room temperature and penetrate into the interior of the polymer, thereby effectively inducing conformational changes in the cross-linked polymer chains within the polymer.
[0154] In addition, when the polar solvent is heated during vapor deposition, the vapor deposition rate can be increased. At this time, the heating temperature is not particularly limited, as long as it is a temperature at which the polar solvent can undergo a phase change into a vapor, for example, it can be 30°C to 80°C. General PEO melts at 60°C, but when a PEO-based copolymer modified with a crosslinkable functional group forms a crosslinked structure, its heat resistance is improved and can withstand up to 80°C, thereby further increasing the vapor deposition rate. In addition, the heating method is not limited, as long as it is a method that can supply energy to generate steam. For example, a direct heating method using a burner or a furnace or an indirect heating method using a heater or a steam pipe, etc., can be used, but the method is not limited to these examples.
[0155] During heating, when the heating temperature is too high, there are disadvantages that the solvent may boil at a temperature above the boiling point of the polar solvent, or a structural change of the solvent may occur, or deformation of the polymer may be caused, and it is difficult to control the evaporation rate of the polar solvent during vapor deposition. Therefore, in order to perform vapor deposition with a trace amount of a polar solvent, it is desirable to perform vapor deposition at a heating temperature within the appropriate range specified above.
[0156] A polymer solid electrolyte as described above may be prepared which contains a polar compound as a polar solvent molecule bonded to chains of a cross-linked polymer via vapor deposition or contained in an internal space between polymer chains.
[0157] According to the method for preparing the polymer solid electrolyte, based on the correlation between the vapor deposition time and the ionic conductivity of the polymer solid electrolyte defined by Equation 1, the degree of improvement of the ionic conductivity of the polymer solid electrolyte can be maximized in the vapor deposition step (S2).
[0158] Preparation method of composite solid electrolyte
[0159] According to another embodiment of the present disclosure, a method for preparing a composite solid electrolyte further comprising a ceramic compound is provided.
[0160] The preparation method of the composite solid electrolyte may be the same as the preparation method of the polymer solid electrolyte of one embodiment described above, except that a ceramic compound is added, and σ in Equation 2 is i,0 1mS / cm or more and less than 10mS / cm,
[0161] The preparation method of the composite solid electrolyte comprises the following steps:
[0162] (S1) mixing a PEO (polyethylene oxide)-based copolymer containing a cross-linkable functional group with a ceramic compound, and then subjecting the PEO-based copolymer contained in the mixture to a cross-linking reaction; and
[0163] (S2) vapor-depositing a polar solvent onto the mixture containing the polymer cross-linked in step (S1),
[0164] The vapor deposition step is performed for a period of time satisfying the following equation 2:
[0165] <Equation 2>
[0166]
[0167] Where, in equation 2,
[0168] σ i (t) is the ionic conductivity of the composite solid electrolyte as a function of vapor deposition time,
[0169] σ i,0 is the maximum ionic conductivity, which is greater than 1 mS / cm and less than 10 mS / cm,
[0170] t is the vapor deposition time, and
[0171] τ is the relaxation time of the polymer chain, which is 12 hours or more and 120 hours or less.
[0172] Meanwhile, except for the addition of the ceramic compound and Equation 2, the procedure and conditions of each step are the same as those of the above-mentioned embodiment of the present invention, and thus further description thereof will be omitted.
[0173] In another embodiment of the preparation method, the ceramic compound has lithium ion transport capability to improve the conductivity of lithium ions, and preferably contains lithium atoms but does not store lithium, and has the function of transporting lithium ions, and can improve the ionic conductivity of the composite solid electrolyte.
[0174] In addition, the ceramic compound can be contained in the internal space of the cross-linked polymer chain in a uniformly dispersed state, such as in a three-dimensional network structure. The ceramic compound is added together during the cross-linking process and can be uniformly dispersed without aggregation in the internal space of the polymer chain formed by cross-linking. This ceramic compound can be beneficial to improve the mechanical strength and ionic conductivity of the composite solid electrolyte due to its uniform dispersion form.
[0175] In addition, the ceramic compound may be in the form of particles. Due to the morphological characteristics of the particles, they may be contained in the composite solid electrolyte in a more uniformly dispersed state. The particles of the ceramic compound may be spherical, and their diameter may be 100 nm to 1000 nm. If the diameter is less than 100 nm, the effect of non-crystallization due to reduced polymer crystallinity may be small, and if the diameter is greater than 1000 nm, the dispersibility may be reduced due to increased aggregation between particles, which may make it difficult to disperse uniformly.
[0176] The ceramic compound may be an oxide or phosphate compound, for example, an oxide solid electrolyte in the form of a lithium metal oxide or a lithium metal phosphate. More specifically, the ceramic compound may be selected from garnet-type lithium lanthanum zirconium oxide (LLZO, Li7La3Zr2O 12 ) compounds, perovskite-type lithium lanthanum titanium oxide (LLTO, Li3xLa 2 / 3-x TiO3) compounds, phosphate NASICON type lithium aluminum titanium phosphate (LATP, Li 1+x Al x Ti 2-x (PO4)3) compounds, lithium aluminum germanium phosphate (LAGP, Li 1.5 Al 0.5 Ge 1.5 At least one of the group consisting of lithium lanthanum zirconium titanium oxide (LLZTO) compounds. More preferably, at least one oxide solid electrolyte selected from the group consisting of lithium lanthanum zirconium oxide (LLZO), lithium silico-titanium phosphate (LSTP), lithium lanthanum titanium oxide (LLTO), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP) and lithium lanthanum zirconium titanium oxide (LLZTO) can be used.
[0177] Oxide or phosphate oxide solid electrolytes usually have a high -4 ~10 -3 S / cm ionic conductivity value, and has the advantages of being stable in the high voltage region and in air, and therefore easy to synthesize and handle.
[0178] Therefore, the above-mentioned composite solid electrolyte may further include a ceramic compound to compensate for the disadvantages involved in the polymer-based solid electrolyte.
[0179] In addition, ceramic compounds are not prone to combustion or ignition even at high temperatures above 400°C, so they have high high-temperature stability. Therefore, when the composite solid electrolyte contains a ceramic compound, it can not only improve the mechanical strength of the composite solid electrolyte, but also improve its high-temperature stability and ionic conductivity.
[0180] The ceramic compound may be included in an amount of 10 to 100 parts by weight, or 10 to 60 parts by weight, based on 100 parts by weight of the PEO-based copolymer containing a cross-linkable functional group.
[0181] If the content of the ceramic compound is too small, the effect of reducing the crystallinity of the polymer and making it amorphous caused by the ceramic compound will be reduced, so the effect of improving the ionic conductivity of the composite solid electrolyte is not significant, and the mechanical properties may not reach the expected level due to the formation of the composite material.
[0182] If the content of the ceramic compound is too high, the ceramic compound cannot be uniformly dispersed in the polymer, and the ceramic compound particles may agglomerate and aggregate with each other, thereby preparing a composite solid electrolyte with reduced ion conductivity.
[0183] Polymer (or composite) solid electrolyte
[0184] The polymer solid electrolyte prepared according to the above embodiment includes: a polymer comprising a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group; and a polar compound, wherein at least a portion of the cross-linkable functional groups of the copolymer form cross-linked bonds with each other, so that the polymer forms a three-dimensional network structure, and wherein the polar compound is contained in the three-dimensional network structure in a gaseous state or may have a structure bonded to a polymer chain.
[0185] Furthermore, in the polymer solid electrolyte, at least a portion of the cross-linkable functional groups may form a cross-linked bond with each other via a cross-linking agent, and the polymer solid electrolyte may further include a lithium salt.
[0186] In addition, the polymer solid electrolyte may be a composite solid electrolyte further including a ceramic compound.
[0187] Meanwhile, the type and content of each component of the polymer solid electrolyte or the composite solid electrolyte have been described above, and thus further description thereof will be omitted.
[0188] In a specific example, the gaseous polar compound may be dispersed between polymer chains forming a three-dimensional network structure, or may have a conformation of being adsorbed or bonded to the surface or interior of the polymer chain.
[0189] This polar compound is a gas molecule of a polar solvent used in the vapor deposition process, and can be contained in the form that the gas molecule of the polar solvent is adsorbed onto the polymer during vapor deposition and then diffused into the polymer chain. As a result, it can be prepared into a solid electrolyte having the above structure. The polar compound is bonded to the polymer chain or contained in the internal space between the polymer chains in a dispersed form, thereby being able to improve the ionic conductivity of the polymer solid electrolyte finally prepared.
[0190] The above-mentioned composite solid electrolyte does not substantially contain a liquid solvent or electrolyte, but contains a trace amount of polar compounds contained or bonded in a gaseous state by vapor deposition. The solid electrolyte can be confirmed from the following facts: for example, when the electrolyte layer containing the solid electrolyte is separated from the all-solid-state battery and then observed with the naked eye or an electron microscope, no liquid component is observed on the surface of the electrolyte layer. In contrast, when a liquid polar solvent or electrolyte is injected into the solid electrolyte, a liquid component or a component showing wettability can be observed on the surface of the electrolyte layer. In addition, the solid electrolyte in which the polar compound is vapor-deposited and contained in a gaseous state exhibits a significantly higher ionic conductivity than when a liquid polar solvent or electrolyte is injected. Even by comparison of such ionic conductivity, the solid electrolyte in which the polar compound is vapor-deposited and contained in a gaseous state can be confirmed.
[0191] Specifically, polar compounds bonded to polymer chains or contained in the internal space between polymer chains can be used as plasticizers and plasticize polymers. Plasticized polymers can have increased amorphous regions in their interiors, thereby improving the mobility of polymer chains. As the mobility of polymer chains increases, the ion hopping effect inside the polymer increases, which can improve the ionic conductivity of polymer solid electrolytes.
[0192] In addition, polar compounds can be used as intermediates for smooth ion transport through ion hopping. Since the affinity between lithium ions and polar compounds is stronger than the affinity between lithium ions and the ether oxygen of PEO-based copolymers, the transmission of lithium ions within the polymer adsorbing polar compounds may be faster and easier. That is, as the polar compound flows into the interior of the polymer, the cationic solvation effect of lithium ions increases to improve ion mobility, thereby improving the ionic conductivity of the polymer solid electrolyte.
[0193] In addition, the polar compound may include at least one selected from the group consisting of carbonate-based compounds and sulfonyl-based compounds.
[0194] Specifically, the polar compound may include at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane, or may include a combination thereof.
[0195] Based on the gross weight of the polymer solid electrolyte, the content of the polar compound may include more than 0.1 wt % and less than 10 wt %. For example, the content of the polar compound may be more than 0.1 wt %, more than 1 wt % and less than 2 wt %, or less than 5 wt %, less than 6 wt %, less than 7 wt %, less than 8 wt %, or less than 9 wt %, or less than 10 wt %. When the content of the polar compound is less than 0.1 wt %, it is difficult to cause changes in the chain conformation inside the polymer, and therefore, the ionic conductivity of the polymer solid electrolyte is not improved. When the content of the polar compound is more than 10 wt %, the polymer solid electrolyte has a larger liquid content and therefore has the performance of a semi-solid battery. In addition, due to the gelation of the polymer, the mechanical strength of the polymer solid electrolyte may be reduced.
[0196] All-solid-state battery
[0197] Another embodiment of the present disclosure also relates to an all-solid-state battery comprising the above-mentioned solid electrolyte, wherein the all-solid-state battery comprises a negative electrode, a positive electrode and a solid electrolyte between the negative electrode and the positive electrode, and the solid electrolyte is prepared according to the above-mentioned embodiment.
[0198] Specifically, the solid electrolyte includes a polymer cross-linked with a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group and a gaseous polar compound, and the ionic conductivity is improved by including or bonding the gaseous polar compound and, optionally, uniformly dispersing a ceramic compound, which can be suitable as an electrolyte for an all-solid-state battery.
[0199] Meanwhile, the positive electrode included in the all-solid-state battery includes a positive electrode active material layer, wherein the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0200] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.
[0201] In addition, the positive electrode active material is not particularly limited as long as it is a material that can reversibly absorb and desorb lithium ions, and examples thereof may be layered compounds such as lithium cobalt oxide, lithium nickel oxide, Li[Ni x Co y Mn z M v]O2 (wherein M is any one selected from the group consisting of Al, Ga and In, or two or more thereof; and 0.3≤x<1.0, 0≤y, z≤0.5, 0≤v≤0.1 and x+y+z+v=1), Li (Li a M b-a-b' M' b' ) 2-c A c (wherein 0≤a≤0.2, 0.6≤b≤1, 0≤b'≤0.2 and 0≤c≤0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn and Ti; M' is at least one selected from the group consisting of Al, Mg and B; A is at least one selected from the group consisting of P, F, S and N), or a compound substituted with at least one transition metal; lithium manganese oxide, such as a chemical formula Li 1+y Mn 2-y O4 (where y is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5 and Cu2V2O7; chemical formula LiNi 1-y Ni-type lithium nickel oxide represented by MyO2 (wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); chemical formula LiMn 2-y M y Lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of Li is replaced by alkaline earth metal ions; disulfides; and composite oxides formed by Fe2(MoO4)3, but are not limited thereto.
[0202] In addition, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material may be 40 to 80 weight %. Specifically, the content of the positive electrode active material may be 40 weight % or more or 50 weight % or more, and 70 weight % or less or 80 weight % or less. If the content of the positive electrode active material is less than 40 weight %, the connectivity and electrical properties between the positive electrode active materials may be insufficient, and if the content of the positive electrode active material is greater than 80 weight %, the mass transfer resistance may increase.
[0203] The binder is a component that assists bonding between the positive electrode active material and the conductive material and bonding with the current collector. The binder may include at least one selected from the group consisting of styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and poly(vinylidene fluoride)-hexafluoropropylene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethyl cellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.
[0204] In addition, based on the total weight of the positive electrode active material layer, the content of the binder may be 1 wt % to 30 wt %. Specifically, the content of the binder may be 1 wt % or more or 3 wt % or more, and 15 wt % or less or 30 wt % or less. If the content of the binder is less than 1 wt %, the adhesion between the positive electrode active material and the positive electrode current collector may be reduced, and if the content of the binder is greater than 30 wt %, the adhesion is improved, but the content of the positive electrode active material is correspondingly reduced, which may reduce the battery capacity.
[0205] In addition, the conductive material is not particularly limited as long as it does not cause side reactions in the internal environment of the battery and does not cause chemical changes in the all-solid-state battery but has excellent conductivity. The conductive material may generally be graphite or conductive carbon, and may be, for example, but not limited to, one selected from the group consisting of: graphite, such as natural graphite or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, Denka black, thermal black, channel black, furnace black, lamp black, and summer black; a carbon material having a crystal structure of graphene or graphite; conductive fibers, such as carbon fibers and metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive oxides, such as titanium oxide; conductive polymers, such as polyphenylene derivatives; and mixtures of two or more thereof.
[0206] Based on the total weight of the positive electrode active material layer, the content of the conductive material can generally be 0.5 wt % to 30 wt %. Specifically, the content of the conductive material can be more than 0.5 wt % or more than 1 wt %, and less than 20 wt % or less than 30 wt %. If the content of the conductive material is too low, i.e., less than 0.5 wt %, it is difficult to obtain the effect of improving conductivity, or the electrochemical characteristics of the battery may deteriorate. If the content of the conductive material is too high, i.e., greater than 30 wt %, the amount of the positive electrode active material is relatively small, so the capacity and energy density may be reduced. There is no particular limitation on the method for introducing the conductive material into the positive electrode, and conventional methods known in the prior art can be used, such as coating on the positive electrode active material.
[0207] In addition, the positive electrode current collector supports the positive electrode active material layer and plays a role in transferring electrons between the external wire and the positive electrode active material layer.
[0208] The positive electrode current collector is not particularly limited as long as it does not cause chemical changes in the all-solid-state battery and has high conductivity. For example, the positive electrode current collector can be made of the following materials: copper, stainless steel, aluminum, nickel, titanium, palladium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy, etc.
[0209] In order to improve the bonding strength with the positive electrode active material layer, the positive electrode current collector may have a fine protrusion and depression structure on its surface or may adopt a three-dimensional porous structure. Thus, the positive electrode current collector may be used in any of various forms, including films, sheets, foils, grids, nets, porous bodies, foams, and non-woven fabric structures.
[0210] The positive electrode as described above can be prepared according to a conventional method. Specifically, the positive electrode can be prepared by the following process: a positive electrode active material layer-forming composition prepared by mixing a positive electrode active material, a conductive material and a binder in an organic solvent is coated on a positive electrode current collector and dried, and the current collector is optionally compression molded to increase the electrode density. At this time, as an organic solvent, it is preferred to use a solvent that can make the positive electrode active material, the binder and the conductive material uniformly dispersed and easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropanol, dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidone (NMP) and the like can be mentioned.
[0211] On the other hand, the negative electrode included in the all-solid-state battery includes a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.
[0212] The negative electrode active material may include a material capable of reversibly inserting and deinserting lithium (Li + ) material, a material that can react with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy.
[0213] Able to reversibly insert and deintercalate lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0214] Preferably, the negative electrode active material may be lithium metal, specifically, may be in the form of a lithium metal film or lithium metal powder.
[0215] The content of the negative electrode active material may be 40 to 80% by weight based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40% by weight or more or 50% by weight or more, and 70% by weight or less or 80% by weight or less. If the content of the negative electrode active material is less than 40% by weight, the electrical characteristics may be insufficient, and if the content of the negative electrode active material is greater than 80% by weight, the mass transfer resistance may increase.
[0216] In addition, the binder is the same as described in the above-mentioned positive electrode active material layer.
[0217] In addition, the conductive material is the same as described in the above-mentioned positive electrode active material layer.
[0218] In addition, the negative electrode current collector is not particularly limited as long as it does not cause chemical changes in the corresponding battery and has conductivity. For example, the negative electrode current collector can be made of the following materials: copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy, etc. In addition, similar to the positive electrode current collector, the negative electrode current collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabric structures having fine protrusions and depressions formed on their surfaces.
[0219] The preparation method of the negative electrode is not particularly limited, and can be prepared by forming a negative electrode active material layer on the negative electrode current collector using a layer or film formation method commonly used in the art. For example, methods such as compression, coating, and deposition can be used. In addition, the negative electrode of the present disclosure also includes the case where the battery is assembled in a state where there is no lithium film on the negative electrode current collector and then a metal lithium film is formed on the metal plate by initial charging.
[0220] According to yet another embodiment, a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source are provided.
[0221] Here, specific examples of the device may include, but are not limited to: power tools driven by electric motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV) or plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; or power storage systems, etc.
[0222] Preferred embodiments will be given below so that the present disclosure can be easily understood. However, the following embodiments are for illustrative purposes only, and the scope of the invention is not limited thereto.
[0223] In the following examples and comparative examples, when preparing polymer solid electrolytes and composite solid electrolytes, Example 1 and Comparative Example 1 are carried out by applying the "solvent vapor deposition method" of vapor depositing a polar solvent, and Example 2 and Comparative Example 2 are carried out by applying the "solvent impregnation method" of impregnating the sample with a polar solvent.
[0224] In addition, the solid electrolytes prepared in the following examples and comparative examples all belong to the category of polymer solid electrolytes, but in Example 2 and Comparative Example 2, ceramic compounds are added to Example 1 and Comparative Example 1, and in order to distinguish them, the terms "polymer solid electrolyte" and "composite solid electrolyte" are used respectively.
[0225] Example
[0226] Example 1: Preparation of polymer solid electrolyte
[0227] Step 1) Preparation of polymer containing copolymer
[0228] A polyethylene oxide (PEO) copolymer of the following chemical formula 1a was prepared:
[0229] [Chemical formula 1a]
[0230]
[0231] Wherein, in chemical formula 1a, R1 is -CH2-O-(CH2-CH2-O) k -CH3, R2 is -CH2-O-CH2-CH=CH2, k is 2, the ratio of l:m:n is 85:13:2, and the weight average molecular weight (Mw) of the copolymer is about 2,000,000 g / mol.
[0232] The copolymer of Chemical Formula 1a has an allyl group bonded through an oxymethylene linker as a crosslinkable functional group.
[0233] The polyethylene oxide copolymer was mixed with acetonitrile as a solvent, trimethylolpropane trimethacrylate as a crosslinking agent, benzoyl peroxide as an initiator, and LiTFSI as a lithium salt to prepare a polymer solution, which was then stirred for 24 hours using a magnetic bar. At this time, the polymer solution consisted of the following materials: based on 100 parts by weight of the polyethylene oxide copolymer, 20 parts by weight of trimethylolpropane trimethacrylate as a crosslinking agent, 1 part by weight of benzoyl peroxide as an initiator, and 36.5 parts by weight of a lithium salt, wherein the acetonitrile solvent was used so that the concentration of the polyethylene oxide copolymer as a polymer contained in the polymer solution was 10.4% by weight.
[0234] The prepared polymer solution was solution-cast on the lower substrate of the coin cell, and then dried once at room temperature for 12 hours and then dried twice at 100°C for 12 hours to induce cross-linking bonds, thereby preparing an electrolyte membrane with a thickness of 200 μm.
[0235] Step 2) Preparation of polymer solid electrolyte
[0236] The polymer was attached to the upper plate of the chamber, the lower part of the chamber was filled with EMC solvent, and then naturally evaporated at room temperature for 24 hours, 48 hours, 72 hours and 168 hours to allow EMC (ethyl methyl carbonate) vapor to flow into the polymer attached to the upper part of the chamber. Thus, a polymer solid electrolyte was prepared.
[0237] Example 2: Preparation of composite solid electrolyte
[0238] A composite solid electrolyte is prepared in the same manner as in Example 1, except that in step 1) of Example 1, based on 100 parts by weight of the polyethylene oxide copolymer, 20 parts by weight of trimethylolpropane trimethacrylate as a cross-linking agent, 1 part by weight of benzoyl peroxide as an initiator, 36 parts by weight of a lithium salt, and 40 parts by weight of LSTP as a ceramic compound are mixed to prepare a mixed solution, wherein acetonitrile solvent is used so that the concentration of the polymer polyethylene oxide copolymer contained in the mixed solution is 11.1% by weight, and the concentration of the polymer polyethylene oxide copolymer and the ceramic compound is 14.9% by weight.
[0239] Comparative Example:
[0240] Comparative Example 1: Polymer solid electrolyte containing modified PEO + a large amount of liquid
[0241] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the liquid EMC solvent was directly injected into the polymer solid electrolyte prepared in step 1) of Example 1 for 0.5 hours, 1 hour, 3 hours, 8 hours and 16 hours.
[0242] Comparative Example 2: Composite solid electrolyte containing modified PEO + a large amount of liquid
[0243] A composite solid electrolyte was prepared in the same manner as in Example 2, except that the liquid EMC solvent was directly injected into the composite solid electrolyte prepared in step 1) of Example 2 for 0.5 hours, 1 hour, 3 hours, 8 hours and 16 hours.
[0244] Experimental example
[0245] Experimental Example 1: Confirmation of the correlation between solid electrolyte and vapor deposition time
[0246] Using the following Equations 1 and 2, the correlation between the vapor deposition time and the content of the polar compound contained in the polymer solid electrolyte deposited by the vapor deposition was confirmed.
[0247] The following equation 1 was used for the polymer solid electrolytes of Example 1 and Comparative Example 1, and the following equation 2 was used for the composite solid electrolytes of Example 2 and Comparative Example 2.
[0248] The following equations 1 and 2 are applicable not only when the vapor deposition process is performed but also when the solvent injection process is performed. For the solvent injection process, the vapor deposition time in equation 1 can be replaced by the solvent injection time.
[0249] <Equation 1>
[0250]
[0251] Where, in equation 1,
[0252] σ i (t) is the ionic conductivity of the polymer solid electrolyte as a function of vapor deposition time,
[0253] σ i,0 is the maximum ionic conductivity, which is greater than 0.1 mS / cm and less than 1 mS / cm,
[0254] t is the vapor deposition time, and
[0255] τ is the relaxation time of the polymer chain, which is 12 hours or more and 120 hours or less.
[0256] <Equation 2>
[0257]
[0258] Where, in equation 2,
[0259] σ i (t) is the ionic conductivity of the composite solid electrode as a function of vapor deposition time,
[0260] σ i,0 is the maximum ionic conductivity, which is greater than 0.1 mS / cm and less than 1 mS / cm,
[0261] t is the vapor deposition time, and
[0262] τ is the relaxation time of the polymer chain, which is 12 hours or more and 120 hours or less.
[0263] (1) Measurement of ionic conductivity (σ i (t))
[0264] In Equation 1 and Equation 2, σ i (t) is calculated according to the following equation 3. At this time, the vapor deposition time (t) of Example 1 and Example 2 is 24 hours, 48 hours, 72 hours and 168 hours, respectively, and the solvent injection time (t) of Comparative Example 1 and Comparative Example 2 is 0.5 hours, 1 hour, 3 hours, 8 hours and 16 hours, respectively.
[0265] In order to measure the ionic conductivity of the solid electrolytes prepared in the examples and comparative examples, a 2 A solid electrolyte was formed on the lower substrate of a coin cell, and then SUS was used as a blocking electrode to manufacture a coin cell for measuring ion conductivity.
[0266] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25°C under the conditions of an amplitude of 10 mV and a scan range of 1 Hz to 0.1 MHz, and then the ionic conductivity of the solid electrolyte was calculated according to the following Equation 3.
[0267] [Equation 3]
[0268]
[0269] Wherein, in Equation 3, σi is the ionic conductivity of the solid electrolyte (S / cm), R is the resistance of the solid electrolyte measured by electrochemical impedance spectroscopy (Ω), L is the thickness of the solid electrolyte (μm), and A refers to the area of the solid electrolyte (cm 2 The solid electrolyte sample used had L = 200 μm, A = 1.7671 cm 2 .
[0270] According to Equation 1 and Equation 2, σ is plotted i The correlation diagram between (t) and t Figures 1 to 4 ), and thus determine the fitting parameters τ and σ i,0 .
[0271] Figure 1 and 2 is a graph showing the change in ionic conductivity of the polymer solid electrolyte during solvent vapor deposition of Examples 1 and 2 as a function of vapor deposition time. Figure 3 and 4 is a graph showing changes in ionic conductivity of the polymer solid electrolyte during solvent immersion of Comparative Examples 1 and 2 with the elapse of immersion time.
[0272] refer to Figure 1 and 2 It can be seen that in Examples 1 and 2, polar solvent vapor is deposited and included in the solid electrolyte using the solvent vapor deposition method, thereby showing a trend of increasing ionic conductivity over a long period of time during which the vapor deposition process is performed. In addition, it can be seen that after a certain period of time, the ionic conductivity slowly increases and converges to a specific value.
[0273] On the other hand, reference Figure 3 and 4 , it can be seen that in Comparative Examples 1 and 2, the polar solvent is included in the solid electrolyte using the solvent impregnation method, so that the ionic conductivity increases rapidly at the beginning of the solvent impregnation method, but shows a trend of no longer increasing.
[0274] In the right Figures 1 to 4 When fitting the graph of i,0 , and the results are shown in Table 1 below.
[0275] [Table 1]
[0276]
[0277] Note 1) The ionic conductivity at t = 72 h is considered to be typical because the system is saturated.
[0278] As shown in Table 1, when Example 1 and Comparative Example 1, which are polymer solid electrolytes, are compared, it is confirmed that in Example 1, which is subjected to the vapor deposition process, σ i,0 and τ are significantly higher than those in Comparative Example 1 in which the solvent impregnation method was performed.
[0279] Even in Example 2 and Comparative Example 2 as the composite polymer electrolyte, it was confirmed that in Example 2 in which the vapor deposition process was performed, σ i,0 and τ are significantly higher than those in Comparative Example 2 where the solvent impregnation method was performed.
Claims
1. A method for preparing a polymer solid electrolyte, the method comprising the following steps: (S1) preparing a polymer, wherein a PEO (polyethylene oxide) type copolymer containing a crosslinkable functional group is crosslinked; as well as (S2) vapor-depositing a polar solvent onto the polymer prepared in step (S1), Wherein, the vapor deposition step is performed for a time period satisfying the following equation 1: <Equation 1> Where, in equation 1, σ i (t) is the ionic conductivity of the polymer solid electrolyte as a function of vapor deposition time, σ i,0 is the maximum ionic conductivity, which is greater than 0.1 mS / cm and less than 1 mS / cm, t is the vapor deposition time, and τ is the relaxation time of the polymer chain, which is 12 hours or more and 120 hours or less.
2. The method for preparing a polymer solid electrolyte according to claim 1, wherein: Step (S1) is performed in the presence of one or more additives selected from the group consisting of a cross-linking agent and an initiator.
3. The method for preparing a polymer solid electrolyte according to claim 1, wherein: A lithium salt is further added in step (S1) or before step (S1).
4. The method for preparing a polymer solid electrolyte according to claim 1, wherein: The crosslinkable functional group is bonded to the PEO-based copolymer through an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms, wherein the alkylene linker having 0 carbon atoms represents a single bond, and The cross-linkable functional group is selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.
5. The method for preparing a polymer solid electrolyte according to claim 1, wherein: The PEO (polyethylene oxide) copolymer is a copolymer containing repeating units of the following chemical formulas 1 to 3: [Chemical formula 1] [Chemical formula 2] [Chemical formula 3] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms, R2 represents a substituent formed by bonding one or more crosslinkable functional groups selected from the group consisting of hydroxyl, carboxyl, isocyanate, nitro, cyano, amine, amide, epoxy and allyl groups to the polymer chain via an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms, wherein the alkylene linker having 0 carbon atoms represents a single bond, and l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.
6. The method for preparing a polymer solid electrolyte according to claim 1, wherein: The vapor of the polar solvent is deposited onto the polymer in step (S2) such that the content of the polar solvent is 0.1 wt% or more and less than 10 wt% based on the total weight of the polymer solid electrolyte.
7. The method for preparing a polymer solid electrolyte according to claim 1, wherein: The polar solvent includes at least one selected from the group consisting of carbonate-based solvents and sulfonyl-based solvents.
8. The method for preparing a polymer solid electrolyte according to claim 1, wherein: The polar solvent includes at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane.
9. A method for preparing a composite solid electrolyte, the method comprising the following steps: (S1) mixing a PEO (polyethylene oxide)-based copolymer containing a cross-linkable functional group with a ceramic compound, and then subjecting the PEO-based copolymer contained in the mixture to a cross-linking reaction; and (S2) vapor-depositing a polar solvent onto the mixture containing the polymer cross-linked in step (S1), Wherein, the vapor deposition step is performed for a time period satisfying the following equation 2: <Equation 2> Where, in equation 2, σ i (t) is the ionic conductivity of the composite solid electrolyte as a function of vapor deposition time, σ i,0 is the maximum ionic conductivity, which is greater than 1 mS / cm and less than 10 mS / cm, t is the vapor deposition time, and τ is the relaxation time of the polymer chain, which is 12 hours or more and 120 hours or less.
Citation Information
Patent Citations
Manufacture of polymeric sold electrolyte
JP1994124713A
Workpiece turning device of machine tools
KR1020220132778A
NFT and virtual currency purchase system and method using points
KR1020230136062A